The TEI Assignment in the Literature Classroom: Making a Lord Mayor’s Show in University and College Classrooms - Mark Kaethler (Journal of the Text Encoding Initiative)
This article offers methods for implementing what Diane Jakacki and Katherine Faull identify as a digital humanities course at the assignment level, specifically one using TEI in college and university literature classrooms. The author provides an overview of his in-class activities and lesson plans, which range from traditional instruction to in-class laboratory exercises, in order to demonstrate an approach to teaching TEI that anticipates students’ anxieties and provides a gradual means of learning this new approach to literary texts. The article concludes by reflecting on how TEI in the classroom complicates critiques of the digital humanities’ proclivity to endorse neoliberal education models. By challenging simplistic renderings of the field and its tools, and by offering interconnections between TEI and traditional humanities practices, the author aims to supply a conscientious approach to designing TEI assignments to those interested but hesitant to include such assignments.